2006
DOI: 10.4073/csr.2006.9
|View full text |Cite
|
Sign up to set email alerts
|

Work Programmes for Welfare Recipients

Abstract: Background: Welfare-to-work programmes have replaced passive welfare recipiency as a means of fighting poverty in many developed countries during the latest decades. There is a belief that placing welfare recipients into subsidised jobs and/or strengthening their skills and knowledge will help them acquire steady jobs. There has, however, been no systematic review of the effects of such programmes on employment, earnings and welfare payments searching systematically for studies from all parts of the world. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
1
25
0
4
Order By: Relevance
“…A review of 48 activation programmes in the USA (Welfare‐to‐Work programmes in US terminology) reveals small positive effects on earnings and employment. Moreover, it shows that job activation tends to have a greater effect than resource activation (Smedslund et al., 2006). However, other studies indicate that there is a time lapse with respect to certain effects of resourse activation (Greenberg, Ashworth, Cebulla & Walker, 2004; Hotz, Imbens & Klerman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 48 activation programmes in the USA (Welfare‐to‐Work programmes in US terminology) reveals small positive effects on earnings and employment. Moreover, it shows that job activation tends to have a greater effect than resource activation (Smedslund et al., 2006). However, other studies indicate that there is a time lapse with respect to certain effects of resourse activation (Greenberg, Ashworth, Cebulla & Walker, 2004; Hotz, Imbens & Klerman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish study (Dahlberg, Johansson & Mörk, 2008) that examined the effects of the local introduction of stricter activation requirements for SA claimants found a small positive group‐level effect on employment. On the other hand, both in the USA and Europe, voluntary programmes, that is, programmes in which sanctions are not used, tend to have more favourable results than mandatory programmes (Malmberg‐Heimonen, 2005; Smedslund et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The supplemental analysis, then, was conducted by using trim-and-fill method (Smedslund et al, 2006). Consequently, synthesized effect size involving trimmed studies showed a little change in comparison with the existing effect size as TMT-B "0.56", TMT-A "0.50"and UFOV-subtest 2 "0.49".…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are entitled to unemployment insurance benefits or who have pensions of any kind were, however, excluded in Smedslund et al (2006).…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%